Analysis of hydrodilatation as part of a combined service for stiff shoulder. Issue 3 (July 2017) - Sinha, Rajendranath; Patel, Priyesh; Rose, Nicky; Tuckett, John; Banerjee, Anurag N; Williams, John; Aldridge, Stephen; Stuart, Paul
Background: Adhesive capsulitis is a common cause of stiff shoulder and may result in pain and restriction of movement. The study aimed to investigate the role of hydrodilatation of the glenohumeral joint in the management of adhesive capsulitis. Methods: Patients referred from the shoulder clinic underwent hydrodilatation under ultrasound guidance. Of 209 referred for hydrodilatation, 163 underwent the procedure and attended follow-up physiotherapy. Outcome measures were available for 118 patients (58 men and 60 women). Mean age of the study group was 52.6 years. Results: There was a statistically significant improvement in both Oxford Shoulder Score (OSS) and Disability Arm Shoulder Hand Scores (Quick DASH) in the first 4 weeks after the procedure, which was maintained but not improved to the end of the study period. Patients presenting with pain, those who had a history of steroid injections and older patients all had worse functional scores at presentation. Diabetes (both Type I and II), previous physiotherapy, length of history and whether pain or stiffness, or both, were the predominant symptom did not have any statistical significance at presentation. These factors were not predictors of any statistically significant improvement in functional scores. Conclusions: Hydrodilatation results in a significant improvement of symptoms in patients with adhesive capsulitis.